Greenspan and the Greenbook - Robert R. Tchaidze (The Johns Hopkins University, Department of Economics, 2002)
A vast literature has emerged using Taylor rules to analyze monetary policy Although very attractive both theoretically and empirically such rules imply a mechanical response by the policy variable to fundamental ones This study looks for empirical evidence of a more sophisticated monetary policy one which takes into account expected future developments An important piece of information I use is the Greenbook forecast series which are calculated by the Federal Reserve Board's Research Department prior to the Board meetings Using Greenbook forecasts allows calculation of future inflation shocks as expected by the Fed These shocks are significant in the estimated Taylor rule confirming that policymaking is forward-looking In addition using Greenbook forecasts allows one to obtain better real time estimates of the potential output and thus to obtain a more precise characterization of monetary policy.
Keywords: E52; E58; 330; Monetary policy; Taylor rule; real time data; Geldpolitik; Regelgebundene Politik; Taylor-Regel; Inflationserwartung; Schätzung; USA